Synthetic Biology and Metabolic Engineering Approaches and Its Impact on Non-Conventional Yeast and Biofuel Production - Madhavan, Aravind; Jose, Anju Alphonsa; Binod, Parameswaran; Sindhu, Raveendran; Sukumaran, Rajeev K.; Pandey, Ashok; Castro, Galliano Eulogio (Frontiers in Energy Research, 2017)
The increasing fossil fuel scarcity has led to an urgent need to develop alternative fuels. Currently microorganisms have been extensively used for the production of first-generation biofuels from lignocellulosic biomass. Yeast is the efficient producer of bioethanol among all existing biofuels option. Tools of synthetic biology have revolutionized the field of microbial cell factories especially in the case of ethanol and fatty acid production. Most of the synthetic biology tools have been developed for the industrial workhorse Saccharomyces cerevisiae. The non-conventional yeast systems have several beneficial traits like ethanol tolerance, thermotolerance, inhibitor tolerance, genetic diversity, etc., and synthetic biology have the power to expand these traits. Currently, synthetic biology is slowly widening to the non-conventional yeasts like Hansenula polymorpha, Kluyveromyces lactis, Pichia pastoris, and Yarrowia lipolytica. Herein, we review the basic synthetic biology tools that can apply to non-conventional yeasts. Furthermore, we discuss the recent advances employed to develop efficient biofuel-producing non-conventional yeast strains by metabolic engineering and synthetic biology with recent examples. Looking forward, future synthetic engineering tools’ development and application should focus on unexplored non-conventional yeast species.